Incorporation of chitosan-stabilized green tea pickering nanoemulsion into hybrid semi-refined carrageenan-gelatin films: stability, antioxidant activity, and performance in active food packaging - Arman, Abdullah; Khadijah Husna, Abd Hamid; Chiew, Wei Nee; Albarqouni, Yasin M.Y.; Nurul Aini, Mohd Azman (Malaysian Institute of Chemistry, 2026)
The environmental impact of plastic packaging calls for innovative, sustainable alternatives for food preservation. This study addresses this critical need by developing novel hybrid semi-refined carrageenan-gelatin films enriched with chitosan-stabilized green tea extract and pickering oil nanoemulsions (PN-GTE/O) with the aim of improving active food packaging. PN-GTE was produced by incorporating green tea extract and soybean oil in a 1:1 ratio. GTE, which was stored for 63 days, was stable in terms of particle size and PDI value at both refrigeration and room temperature. Plasticized carrageenan and gelatin were prepared with different PN-GTE concentrations for the formulation of active food packaging. The films were characterized by FTIR analysis, which confirmed the incorporation of the bioactive GTE compounds by hydrogen bonding between chitosan and polyphenols. The mechanical properties were significantly affected by the PN-GTE concentration in the active films, with 10% PN-GTE showing a remarkably high tensile strength of the film of 4.58 MPa, indicating a transition from interfering inclusions to reinforcing fillers. Physical properties such as film thickness, opacity, solubility and moisture content were also evaluated, demonstrating the suitability of the films for packaging applications. In addition, the films exhibited strong antioxidant activity. 10% of the PN-GTE films achieved up to 60% scavenging of DPPH radicals, confirming their potential for long-lasting oxidative protection. By integrating stable, antioxidant-rich green tea nanoemulsions into biodegradable biopolymer films, a practical and environmentally conscious solution is offered to extend the shelf life of food and ultimately contribute to less food waste and a healthier planet.